NYKAA: A Comprehensive Analysis of a Leading Indian E-Commerce Cosmetic Company - Suchitra; Ramesh Pai, (International Journal of Case Studies in Business, IT and Education (IJCSBE), 2021)
Purpose: The cosmetics industry is one of the major industries that have attracted many players due to its rapid growth. The cosmetics industry plays an important role in developing the country's economy. This study is being taken up to better understand the contribution of the beauty industry to the development of the country and to evaluate the strategies of these companies. Nykaa is one of the leading companies in the cosmetics industry. It offers various products of different brands on one platform. Its setup by Falguni Nayar in 2012. She anticipated the huge opportunity in online trading in the coming years and converted that opportunity into a big vision. Her decision was not wrong it turned into building a large-scale business. By operating multinational, it attracts customers from various regions. Initially, it started the business by offering beauty products later on diversified with fashion, skincare, luxury products. This study is conducted to evaluate the strategies used by NYKAA to be one of the top companies in E-Commerce. Research Methodology: In this paper, an attempt is made to evaluate financial performance, Competitor’s analysis, CSR, Marketing and Inventory strategy, SWOC framework of Nykaa as a research case study. Findings: From the study, it’s clear that Nykaa is doing very well in E-retailing and gives tough competition to rival firms. Giving a platform to small entrepreneurs to grow along with their successful journey. Originality: Various performance analysis techniques are used to appraise the NYKAA accomplishment. Paper type: Research Case study.